Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00701-005-0617-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after decompressive craniectomy in patients with severe ischemic stroke

Abstract: Decompressive craniectomy after space occupying infarction of the middle cerebral artery (MCA) tends to decrease mortality and increase functional outcome. The aim of this retrospective study was to evaluate mortality rates and functional outcome in our centre and to identify predictors of prognosis. The charts of 30 consecutive patients (6 women, 24 men, mean age 59.3 +/- 11.0 years) who underwent craniectomy after space occupying MCA-infarction from 1996 to 2002 were analyzed. Functional outcome was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 30 publications
2
36
0
10
Order By: Relevance
“…Even though they could show a reduction in mortality in the surgical group (33% vs. 75%), the neurological outcome was poor [39]. Their results were supported by several clinical series [31,33,34,41,42,43,58,59]. In a review Arac et al reported about 273 patients from 19 studies showing a mortality rate of 51% in the sub-group analysis of patients older than 60 years versus 21% in younger patients, associated with a significantly larger number of patients with poor neurological outcomes in the subgroup >60 years (81.8% vs. 33.1%) [60].…”
Section: Surgical Treatmentsupporting
confidence: 58%
See 2 more Smart Citations
“…Even though they could show a reduction in mortality in the surgical group (33% vs. 75%), the neurological outcome was poor [39]. Their results were supported by several clinical series [31,33,34,41,42,43,58,59]. In a review Arac et al reported about 273 patients from 19 studies showing a mortality rate of 51% in the sub-group analysis of patients older than 60 years versus 21% in younger patients, associated with a significantly larger number of patients with poor neurological outcomes in the subgroup >60 years (81.8% vs. 33.1%) [60].…”
Section: Surgical Treatmentsupporting
confidence: 58%
“…The impact of the dominant hemisphere is not sufficiently considered in available studies of malignant MCA infarction, and moreover, most studies include a mixture of dominant and nondominant stroke patients, or even mention only the number of patients with aphasia. The present overview shows the rate of dominant-hemispheric infarction represented in the literature: Holtkamp et al (both sides without differentiation) [39], Skoglund et al (17%) [35], Foerch et al (19%) [33], Maramattom et al (22%) [29], Rabinstein et al (24%) [59], Robertson et al (25%) [32], Harscher et al (27%) [41], Yao et al (32%) [63], Weil et al (36%) [64], Chen et al (37%) [34], Jüttler et al (37%) [12], Jüttler et al (38%) [8], Hofmeijer et al (38% aphasia) [7], Zhao et al (38%) [11], Wang et al (38%) [28], Koh et al (43%) [65], Walz et al (44%) [42], Malm et al (47%) [30], and Kiphuth et al (57%) [66], Vahedi et al (60% aphasia in the conservative arm, and 55% in the surgical arm, as an outcome parameter) [10], Vahedi et al (60% survivors with aphasia after 1 year) [9]. Only few studies found a difference in outcome after malignant MCA infarction that is influenced by the side of the lesion.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Large decompressive craniotomies are performed to reduce secondary insults related to intracranial hypertension due to severe head injury or cerebral infarction (Aarabi et al, 2006;Harsher et al, 2006). After treatment in the acute stage, cranioplasty is performed for aesthetic and protective reasons.…”
Section: Introductionmentioning
confidence: 99%
“…This type of extensive stroke has been termed malignant MCA infarction and is accompanied by severe brain edema, leading to raised ICP and subsequent brain herniation. 5 A vicious cycle develops as the resulting ischemic insult leads to further edema, and thus to increases in ICP and reduction of regional cerebral blood 6 Medical treatment has not been shown to be effective. 7 Several experimental studies 8,9 have shown the benefit of decompressive craniectomy in rats after MCA occlusion.…”
Section: Introductionmentioning
confidence: 99%